2015
DOI: 10.1002/ejhf.252
|View full text |Cite
|
Sign up to set email alerts
|

Nurse‐coordinated collaborative disease management improves the quality of guideline‐recommended heart failure therapy, patient‐reported outcomes, and left ventricular remodelling

Abstract: BackgroundHeart failure (HF) pharmacotherapy is often not prescribed according to guidelines. This longitudinal study investigated prescription rates and dosages of angiotensin-converting enzyme inhibitors/angiotensin receptor blockers (ACEi/ARB), beta-blockers, and mineralocorticoid receptor antagonists (MRA), and concomitant changes of symptoms, echocardiographic parameters of left ventricular (LV) Methods and resultsThe INH study evaluated a nurse-coordinated management, HeartNetCare-HF TM (HNC), against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(55 citation statements)
references
References 46 publications
3
46
1
5
Order By: Relevance
“…Dosages of beta‐blockers, renin‐angiotensin system (RAS) antagonists and MRA were significantly higher at 3‐month follow‐up compared to hospital discharge and were comparable to a recent randomized study on optimization of heart failure medication management 22. We found that delayed improvers had significantly higher dosages of MRA than nonimprovers.…”
Section: Discussionsupporting
confidence: 65%
“…Dosages of beta‐blockers, renin‐angiotensin system (RAS) antagonists and MRA were significantly higher at 3‐month follow‐up compared to hospital discharge and were comparable to a recent randomized study on optimization of heart failure medication management 22. We found that delayed improvers had significantly higher dosages of MRA than nonimprovers.…”
Section: Discussionsupporting
confidence: 65%
“…While lower quality of HF treatment was associated with higher or increasing MR‐proADM, patients on higher ACEi/ARB and beta‐blocker doses at baseline and F6 had lower levels of this biomarker. This is consistent with findings that patients with a higher comorbidity burden tolerate up‐titration of guideline‐recommended cardiac drugs less well . Additionally, reverse LV remodelling was significantly more common in study participants with consistently low MR‐proADM levels.…”
Section: Discussionsupporting
confidence: 53%
“…As key members of the multidisciplinary team, they are responsible for the 24 h monitoring of patients admitted with AHF ensuring effective communication among professionals as well as education and support to patients and caregivers. Over recent years, evidence has shown the value of nurse‐led interventions, in terms of improved survival and quality of life as well as reduced length of hospital stay and rates of readmission . Reviewing patients during the critical post‐discharge phase (7–14 days) enables evaluation of clinical status and patient's self‐management behaviours.…”
Section: Role Of Nursing In Clinical Monitoringmentioning
confidence: 99%